2019
DOI: 10.1109/access.2019.2913466
|View full text |Cite
|
Sign up to set email alerts
|

Wideband MIMO Antenna Systems Based on Coupled-Loop Antenna for 5G N77/N78/N79 Applications in Mobile Terminals

Abstract: A wideband 8-antenna multiple-input and multiple-output (MIMO) system that can cover 3.3-5.0 GHz is proposed for the 5G new radio N77/N78/N79 application in mobile phones. The wide bandwidth of the MIMO antenna system is obtained by the proposed coupled-loop antenna, which has three coupling sections located separately at its top central and two sides. Due to this special arrangement, the coupled-loop antenna can support three resonance modes of loop antenna: 0.5λ, 0.75λ, and 1.0λ modes. The distinctive featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 29 publications
1
88
0
Order By: Relevance
“…As seen, the design has less than − 20 dB TARC values at different frequencies. The fundamental properties of the proposed MIMO diversity antenna system are compared with the recently reported MIMO antenna designs and are listed in Table 3 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. As clearly seen, in contrast to the recently proposed designs, the designed MIMO antenna offers ultra- Another important function is the channel capacity loss (CCL) of the MIMO system [43], which mainly depends on the S-parameters of the MIMO system with the accepted limit of ≤0.4 bps/Hz and can be calculated while using the below formulas:…”
Section: The Proposed Uwb Diversity Antenna Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen, the design has less than − 20 dB TARC values at different frequencies. The fundamental properties of the proposed MIMO diversity antenna system are compared with the recently reported MIMO antenna designs and are listed in Table 3 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. As clearly seen, in contrast to the recently proposed designs, the designed MIMO antenna offers ultra- Another important function is the channel capacity loss (CCL) of the MIMO system [43], which mainly depends on the S-parameters of the MIMO system with the accepted limit of ≤0.4 bps/Hz and can be calculated while using the below formulas:…”
Section: The Proposed Uwb Diversity Antenna Systemmentioning
confidence: 99%
“…Several MIMO 5G smartphone antennas have been recently proposed [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. However, these smartphone antennas either suffer from narrow impedance-bandwidth (either single-band or dual/multi-band) or use single-polarized uniplanar antenna resonators occupying large spaces of the mainboard, which leads to increasing the complexity of the mobile phone system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a self-decoupled MIMO antenna set [31] is accomplished by merely integrating a popularly used loop antenna [32][33][34] with a conventional ground-radiation antenna. It is revealed that the loop is equivalent to an array of two parallel electric-current sources, and the groundradiation antenna is equivalent to a magnetic-current source; this orthogonality contributes to the high isolation property with no need for any additional structural support or tuning efforts.…”
Section: Introductionmentioning
confidence: 99%
“…However, the frequency bands are independently separated. In [10], an 8-unit broadband MIMO antenna system was proposed, and there were three coupling parts in the antenna. Regulating the length of the coupling part, the loop antenna can work at 0.5λ, 0.75λ, 1.5λ, and finally cover 3.3-5.0 GHz.…”
Section: Introductionmentioning
confidence: 99%